Pengaruh Nilai Tukar Rupiah, Produksi Domestik Kakao, Dan Luas Lahan Terhadap Ekspor Kakao Indonesia Tahun 1995-2015 - ARTIKA, RULLY, Ir. Maulidyah Indira Hasmarini M.Si (2017)
This study examines the influence of the rupiah exchange rate, domestic production of cocoa, and land area on Indonesian Cocoa Exports in the short term and long term. The this ressearch used a secondary data from the years 1995 to 2015 times series. Data source were obtained from the official website of Badan Pusat Statistik Indonesia and Kementerian Perdagangan Indonesia. The analytical method used was error correction model (ECM). The results indicates that rupiah exchange rate, domestic production of cocoa and land area insignificant influecne in the short term on Indonesian Cocoa Exports. Domestic production of cocoa in the long term indicates that insignificant influence on Indonesian Cocoa Exports, while the rupiah exchange rate and land area has significant effect on Indonesia Cocoa Exports. The coefficient of determination value is 0,629999 whict means that rupiah exchange rate, domestic production of cacao and land area affects 62,99% of the Indonesian Cocoa Exports. According to the results of simultaneous test (F test), indicating that rupiah exchange rate, domestic production of cocoa has significant effect on Indonesia Cocoa Exports simultaneous.